4CPS-179 Use of specific drugs for dementia in people at the end of life in nursing homes. (March 2019) - Zurutuza, A; Beobide, I; Miró, B; Ferro, A
Abstract : Background: Acetylcholinesterase inhibitors (ACEIs) and memantine are drugs used in Alzheimer's disease (AD) and dementia with Lewy bodies or associated to Parkinson's disease (LB-P). Their efficacy is limited and deprescription strategies are necessary when clinical, functional decline, advanced dementia and/or end of life occurs. Purpose: To evaluate the use of anti-dementia drugs of institutionalised people who died throughout a year in the nursing homes studied. Material and methods: Retrospective analysis of patients who died in seven nursing homes between July 2017 and June 2018. We analysed the Global Impairment Scale (GDS-FAST), the Barthel Index (BI), anti-dementia drugs and their withdrawal prior to the death of people diagnosed with dementia. The data were obtained from the electronic prescription system and analysed with SPSS v20. Results: Among 1125 people attended during the analysed period, 183 (16.3%) died, identifying 128 (69.94%) cases of dementia. Of these, 56% were female, with a mean age of 89.9 (s=6.54) for females and 84 (s=6.9) for males, and the median stay was 613 days (IQR 1679). Cognitive and functional assessments were: GDS-FAST median 6 (IQR 1) and BI median 17 (IQR 32). The distribution of dementias had the following pattern: AD 51 (39.8%), vascular dementia 14 (10.9%), LB-P six (4.7%), mixed dementia three (2.3%), frontotemporal dementia two (1.6%) and other types 52 (40.6%). Forty-one (32%) patients had a specific drug for dementia during their stay: ACEIs 27 (65.9%), memantine nine (22%) and ACEIs +memantine five (12.2%). 73.2% of patients diagnosed with AD or LB-P had been prescribed one of these drugs. Eighty-five per cent and 70% of the patients persisted with their treatment in the past 12 and 6 months, respectively. The median number of days from the suspension of the drugs to death was 11 (IQR 259.5). For this analysis, four cases with a stay shorter than 30 days were excluded. Conclusion: A high percentage of patients had been prescribed anti-dementia drugs close to their death. We have to do an early identification of patients at the end of life and re-evalute the effectiveness of these drugs during this period, applying if necessary, deprescription strategies. References and/or acknowledgements: No acknowledgements. No conflict of interest.